Effects of Dietary Fats on Immune System Response in Covid-19 - özkaya, ismail; bozay, kübra (Puerto Rico Health Sciences Journal, 2022)
Coronavirus disease 2019 (COVID-19), which is affecting people around the globe, is a respiratory disease that is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and that has reached the pandemic state. It is known that people who are vulnerable but who are not immunocompromised can still suffer from serious complications of COVID-19. The general nutritional status and food consumption patterns of each individual affect the functioning of his or her immune system. The effects of these patterns can occur at the level of physical barriers, the microbiome, the innate immune system, and the adaptive immune system. Immune system cells and mediators, which are essential to the inflammatory response, are in the structures of proteins, fats, and carbohydrates and act through vitamins and minerals. The combination of chronic infection and malnutrition disrupts the immune response, affects the amount of immune cells, and increases inflammatory mediators. Dietary fat (in terms of both amount and type) affects cytokine biology, making the former a key player in inflammatory disease; also having an important role as macronutrients, because of how they affect immune cells and function. This review explores the role of dietary fat in the immune response, highlighting the role in protecting the individual from COVID-19 and mitigating the cytokine storm in the infection phase.